1999
DOI: 10.1021/la990070n
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Deposition of Inorganic Clusters from Micellar Block Copolymer Films

Abstract: A method is presented for generating quasiregular arrays of nanometer-sized noble metal and metal oxide clusters on flat substrates by the use of a polymer template. The approach is of general applicability to other metals and various oxides. In the first step, polymeric micelles with a polar core were generated by dissolution of poly(styrene)-block-poly(2-vinylpyridine) in toluene. These micelles were used as nanocompartments that were loaded with a defined amount of a metal precursor. The metal ions can be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
627
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 605 publications
(640 citation statements)
references
References 38 publications
10
627
1
2
Order By: Relevance
“…Me-containing micelles as sacrificial layer very fast very high (no lower limit) very low low [119] , [120] Non- very low high [121] Theory 41…”
Section: Micellar Lithographymentioning
confidence: 99%
See 1 more Smart Citation
“…Me-containing micelles as sacrificial layer very fast very high (no lower limit) very low low [119] , [120] Non- very low high [121] Theory 41…”
Section: Micellar Lithographymentioning
confidence: 99%
“…[119] They used block-copolymer micelles of polystyrene-poly(2-vinylpyridine) that were charged with auric acid during the assembly process. After assembly into a two-dimensional crystal on a solid substrate, a plasma etching procedure was applied to remove the organic compounds and to reduce the auric acid to inorganic gold nanoparticles.…”
Section: Micellar Lithographymentioning
confidence: 99%
“…[21][22][23][24] Varying the molecular weight of diblock copolymers causes variations in lateral spacing between the gold nanoparticles. Here, we demonstrate that the lateral spacing of gold nanoparticles also depends on the concentration of the micellar dipcoating solution and on the substrate retraction velocity, the latter of which enables the formation of well-defined nanoparticle spacing gradients.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…We found that the morphology of selfassembled thin films can be controlled much easier, if the precursor loaded material PS-b-P[4VP(HAuCl 4 )] (Step II) is used to deposit the films prior to the reduction step. Subsequently, different methods such as wet-chemical processes, [22] UV irradiation, [23] or O 2 -plasma etching [24] can be applied to generate Au-nanoparticles.…”
Section: Preparation Of Organic-inorganic Hybrid Nanostructuresmentioning
confidence: 99%